Variabilitas Genetik dan Heritabilitas 20 Genotipe Tanaman Cabai (Capsicum annuum L.) Unggul Koleksi Ipb - Romadhoni, Anggi; Zuhry, Elza; ', Deviona (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Study lasted from June until November 2011, at Bogor Agricultural University (IPB), Leuwikopo, Dramaga. This research using Randomized Complete Block Design (RCBD), one factor consisting of 20 genotypes of chilli that comes from the collection of IPB (C2, C5, C105, C111, C117, C118, C120, C160, C51, F5110005-91-13-5, F5110005-91-13-12, C157, C159, F5120005-5-11-1, F8002005-2-9-12-1, C140, C19, C18, C143, C145) with three replications. Data were analyzed using the F test and test of Duncan New’s Multiple Range Test (DNMRT) 5% level. Result shows that the genetic variability and heritabilty of 20 genotypes chilli in quantitative parameters were different each other.Genotypic coeffecients of variation (GCV) at intervals between 1,36 -22,11%. The heritability value at intervals 42.05%-91.80%. Almost all of the observed variables had high heritability value, except leaf length and flowering date which is only on intermediate criteria. For weight per fruit, C143 reveal significant value than other genotype and yield per plant C5 reveal significant value than the others. It indicate that C143 and C5 can be selected as Hybrid chilli plant. The genotypes tested in this study had a high level of variability that could potentially be used as a parent for crosses. Meanwhile, the 20 genotypes that observed qualitiatively shows it genetic relationship. Keywords : genotypic coeficient of variation, variability, heritability, phenotipic variance.